Determinants of employee job satisfaction: The roles of career development, compensation, and work-life balance - Herdiani, Osnita Barlianty; Dian Surya (Sekolah Tinggi Ilmu Ekonomi Indonesia Jakarta, 2024)
This study aims to analyze the determinants of employee job satisfaction at PT. Madya Putera Tehnik focuses specifically on career development, compensation, and work-life balance. Employing a quantitative approach with a survey method, this research collected data from all 132 employees through a saturated sampling technique. The data were analyzed using the Partial Least Squares (PLS) method. The findings reveal that compensation and work-life balance have positive and significant effects on job satisfaction, while, surprisingly, career development shows no significant impact on employee job satisfaction. These results suggest that employees at PT. Madya Putera Tehnik places greater importance on immediate financial rewards and work-life harmony than on long-term career progression. The study provides valuable insights for the company's human resource management in developing more effective strategies to enhance employee satisfaction, particularly through compensation system improvements and work-life balance programs. Article Information:Received 9/28/2024 / Revised 11/15/2024 / Accepted 12/20/2024 / Online First 12/25/2024